If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -4cosx = -3 Solving 1 + -4cosx = -3 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4cosx = -3 + -1 Combine like terms: 1 + -1 = 0 0 + -4cosx = -3 + -1 -4cosx = -3 + -1 Combine like terms: -3 + -1 = -4 -4cosx = -4 Divide each side by '-4osx'. c = o-1s-1x-1 Simplifying c = o-1s-1x-1
| 73=-6g+97 | | 33.6=H^3/2 | | 8p=97 | | j+23=3 | | 12=6a+2 | | 3x+7y+23=30 | | m=(h-w)/8 | | 7=6c+1 | | 3+4(t+2)=2t-2 | | -y+244=179 | | j+23=-s | | 11+4x+2+3x=90 | | P-3+8=8 | | 0.5(3z+7)+17.7=0.7(3z-4) | | -0.72m=-2 | | 73=9h+1 | | A+B=4X-2 | | 14-3p+1=4+p | | 3.33=-.5 | | 185=35-x | | 750+0.2=1050 | | A+B=4X-8 | | (5.3x+8.2y)+(13.3y-4.1x)= | | 0=8n+7n | | 5x-7.1111=64 | | 3x+7x-3.5=2 | | x-10+2x+30=180 | | 25x-10+58=180 | | 6(5x+5)+4x= | | y-4x=-14 | | 3/8*16= | | 2(d+1)=-38 |